Desenvolvimento e análise de uma unidade de ensino potencialmente significativa para o ensino da teoria da relatividade restrita - Martins, Claudinéia de Oliveira (2019)
The literature on Physics Teaching reports obstacles to the insertion of topics of Modern and Contemporary Physics in high school, being those of epistemological and didactic character or linked to the formation of teachers. In order to contribute to this field of study this work seeks to develop, apply and evaluate a Potentially Meaningful Teaching Unit to support the teaching of concepts of the Theory of Restricted Relativity. The proposed Potentially Meaningful Teaching Unit is based on the principles of Ausubel's Theory of Meaningful Learning. We chose the theme of Relativity, because the literature that investigate the mechanisms involved in the process of knowledge construction in real classroom conditions is scarce. The implementation of the Potentially Meaningful Teaching Unit aims to investigate whether there are indicative of the conceptual evolution of the group of people participating in the proposed activities. The approach used was to hold a teaching workshop on the theme of Theory of Restricted Relativity for a group of teachers, which was evaluated through mental/conceptual maps elaborated before and after the interventions. When comparing the results for these two moments, we observed that the set of activities implemented in the Potentially Meaningful Teaching Unit provided a conceptual evolution in the learning of the workshop participants. It was evident from the analysis of the results presented that activities involving mental and conceptual maps have the ability to lead to an Meaningful Learning. In addition, the Potentially Meaningful Teaching Unit evaluation from the contributions of the participating teachers contributed to improvements in the Potentially Meaningful Teaching Unit aimed at enhancing learning material and finding methods that facilitate students' understanding of the subject in different evaluation tools to seek evidence of how occurs to the evolution of the conceptual, procedural and application fields about Theory of Restricted Relativity along the implementation of the didactic proposal.